TRANSFORMASI PENGGUNAAN JILBAB OLEH ARTIS INDONESIA (2001-2017) - Alfakhruji, Syahid Wizdan; Sulasman; Lestari, Fathia (Sekolah Tinggi Ilmu Adab dan Budaya Islam Riyadul 'Ulum, 2026)
This research analyzes the transformation of hijab usage among Indonesian celebrities from 2001 to 2017. The primary issue addressed is the deconstruction of the hijab's image, which was initially perceived as rigid and a hindrance to professionalism during the New Order era, into a modern and emancipatory popular identity through the strategic role of public figures. The objective of this study is to map the phases of changes in hijab aesthetics and identify the driving factors that transformed this religious attribute into a symbol of international achievement. The methodology employed is the historical research method, encompassing four stages: heuristics through the collection of primary sources in the form of contemporary media clippings (Pikiran Rakyat, Galamedia) and oral sources (interview documentation), source criticism, interpretation, and historiography. The analysis was conducted using Homi K. Bhabha’s theory of cultural hybridity to observe the emergence of a